KARAKTERISTIK ORANG TERSANGKA RABIES DI KLINIK BESTARI MEDAN TAHUN 2011 - Mainan Mutiara S.Pane; Hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
AbstractRabies ( hydrophobia ) is a disease caused by Lyssa zoonosa – virus ( rabies virus ) and istransmitted to human through the bite of rabid animal patients. In 2008 it was reported that thecase of a dog suspected of having rabies that rabies humans as much as 20.926 cases, 104 positiverabies and all of them died ( CFR 100% ). In 2010, the number of cases of rabies in Indonesia withGPHR 78.203 rabies positive cases as many as 206 people and all of them died ( CFR 100% ).Clinic Bestari in Medan in 2011 there were 365 cases of bites HPR in Medan, number of bite casesindicated/ VAR as many as 178 cases and 3 death from rabies (CFR 1.69%).To determine the characteristics of the suspected Rabies Clinic Bestari in Medan in 2011conducted a descriptive study using a case series design. Population of 178 people suspected rabiesand sampled 178 people.Results showed that the highest proportion of people suspected rabies by the age of 2-9years 28.7%, ie gender male 52.8%, where the bite of the legs 32.6%, which is in the bite exposuretype 75.8%, where is the Medan District Tuntungan 22.5%, while the June 14.6%, HPR type of dogthat is 92.7%, which is a complete vaccination status of 82.6%. There is a differences in theproportion of age with suspected Rabies sex with p =0.029 ( <0.05 ), There were age differences inthe proportion of type exposure with p = 0.003 (<0.05 ), There were no differences in theproportion of age with type HPR p value = 0.092 ( >0.05 ), There were no differences in theproportion of vaccine status type exposure with p = 0.0492 ( >0.05 ), statistical analysis of thestatus of the vaccine according to the location of the bite and age according to the location of thebite can not be done with chi – square test because there are 2 cells ( 33.3% ) who expected count<5. Department of Health is expected to increase efforts to educate the public about rabies andreport immediately if the bite, licking at the paws or by HPR. Peer – to clinics to increase the datarecording and reporting of suspected rabies ( VAR, administration, ATS or SAR ).